2011
DOI: 10.17700/jai.2011.2.1.51
|View full text |Cite
|
Sign up to set email alerts
|

Hálózati szolgáltatások használata az egyéni gazdálkodók körében

Abstract: Az információ, mint új termelési tényez? jelent meg az agrárgazdaságban is. A megfelel? információnak a megfelel? id?ben való megléte a gazdálkodás eredményességét jelent?sen meghatározza. Napjainkban az interneten keresztül juthatunk leggyorsabban információhoz, ezért a vidéki területek szélessávú fejlesztése egyre jobban el?térbe kerül. Az agrárvállalkozások számára szintén fontos a szélessávú internet hozzáférés többek között az e-közigazgatás növekv? jelent?sége miatt, hiszen lehet?séget nyújt a törvényi s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Bognár & Galácz 2004, Dessewffy et al 2005, Csótó & Herdon 2008. The age and earlier experience with information technology influenced the adoption and also the intensity of ICT-use among farmers in Hajdú-Bihar county, Hungary (Botos & Cseh 2011). In the same county, the findings of Botos (2014) showed that, the aim of use is reduced only to communication (e-mail) and some information seeking among agriculture SME-s, but the bigger and more diverse enterprises use more applications (e.g.…”
Section: Theoretical Background: Ict-adoption In Agriculturementioning
confidence: 99%
“…Bognár & Galácz 2004, Dessewffy et al 2005, Csótó & Herdon 2008. The age and earlier experience with information technology influenced the adoption and also the intensity of ICT-use among farmers in Hajdú-Bihar county, Hungary (Botos & Cseh 2011). In the same county, the findings of Botos (2014) showed that, the aim of use is reduced only to communication (e-mail) and some information seeking among agriculture SME-s, but the bigger and more diverse enterprises use more applications (e.g.…”
Section: Theoretical Background: Ict-adoption In Agriculturementioning
confidence: 99%